Asymmetric spatial distribution of subsolar metallicity stars in the Milky Way nuclear star cluster. Issue 1 (30th March 2020) - Feldmeier-Krause, A; Kerzendorf, W; Do, T; Nogueras-Lara, F; Neumayer, N; Walcher, C J; Seth, A; Schödel, R; de Zeeuw, P T; Hilker, M; Lützgendorf, N; Kuntschner, H; et al.
ABSTRACT: We present stellar metallicity measurements of more than 600 late-type stars in the central 10 pc of the Galactic Centre. Together with our previously published KMOS data, this data set allows us to investigate, for the first time, spatial variations of the nuclear star cluster's metallicity distribution. Using the integral-field spectrograph KMOS (VLT), we observed almost half of the area enclosed by the nuclear star cluster's effective radius. We extract spectra at medium spectral resolution and apply full spectral fitting utilizing the PHOENIX library of synthetic stellar spectra. The stellar metallicities range from [M/H] = −1.25 dex to [M/H] > +0.3 dex, with most of the stars having supersolar metallicity. We are able to measure an anisotropy of the stellar metallicity distribution. In the Galactic north, the portion of subsolar metallicity stars with [M/H] < 0.0 dex is more than twice as high as in the Galactic south. One possible explanation for different fractions of subsolar metallicity stars in different parts of the cluster is a recent merger event. We propose to test this hypothesis with high-resolution spectroscopy and by combining the metallicity information with kinematic data.